Level of Self-Assessed Entrepreneurial Competence of Students from Accountancy, Business and Management Programs - Astrero, Mark Kevin; Velasco, Joyce Irene R. (Journal of World Economy, 2025)
Entrepreneurial competence in students is vital today, and especially for students taking Accountancy, Business, and Management (ABM) programs. This study evaluated the level of Personal Entrepreneurial Competencies (PECs) of ABM students in Santiago City, Philippines, an opening in the empirical literature for situationally embedded competency assessment in the Philippine educational landscape. Utilizing a quantitative-descriptive approach, the researchers surveyed 300 ABM students from Northeastern College, using validated tools for self-assessing and for learning competencies. It is noteworthy that 81.34% of the respondents exhibited at most satisfactory entrepreneurial skill, of which 34.67% exhibited outstanding skill. Higher proficiency levels were observed for the categories of Risk Taking (68.66%) Demand for Quality and Efficiency (68%), and Goal Setting (70.34%); highest proficiency levels allied well with the student’s inclination to engage in entrepreneurial opportunities; meanwhile, a significant portion of students had only sufficiently moderate levels of competencies embraced in Opportunity Seeking (79.33%) and Persistence (74%); suggesting it may be prudent to introduce further contextual or experiential applications of the pedagogy. This study demonstrates the need for participatory, innovative education programs like mentoring, experiential learning, and redesigning the curriculum dedicated to taking the students from moderate to high entrepreneurial ability. In the Philippines’ socio-economic context, the study emphasizes the importance of starting and growing new businesses as a route to self-employment and for sustainability.